Effects of q-profile structures on intrinsic torque reversals. (5th August 2015) - Lu, Z.X.; Wang, W.X.; Diamond, P.H.; Tynan, G.; Ethier, S.; Chen, J.; Gao, C.; Rice, J.E.
Abstract: Changes in rotation have been observed in LHCD experiments. From these observations, reversals in intrinsic torque have been inferred. This paper identifies the mechanism for intrinsic torque reversal linked to magnetic shear ( ). Gyrokinetic simulations demonstrate that as compared to the normal case, the intrinsic torque reverses, for . Analysis shows that the reversal occurs due to the dominance of the symmetry breaking mechanism in residual stress due to the synergy of toroidal coupling and the intensity gradient. This mechanism is a consequence of ballooning structure at weak . Gyrokinetic simulation gives for trapped electron modes (TEM) and for ion temperature gradient (ITG) modes. The value of is consistent with results from the Alcator C-Mod LHCD experiments, for which in the whole plasma column and (Rice et al Phys. Rev. Lett .111 125003).